Targeted delivery of short hairpin RNA expressing plasmid using hepatitis B virus-like particle for bcl-2 gene silencing in cervical cancer cells - Akwiditya, Made Angga (2021)
Gene therapy research has advanced rapidly to clinical trials, but it is greatly hampered by the unstable nucleic acids particularly short interference RNA (siRNA) packaged inside carriers, and the lack of specificity towards targeted sites in the body. Hence, development of a stable carrier with specific targeted delivery is urgently needed. This study aimed to address gene therapy limitations by encapsidating a plasmid synthesizing short hairpin RNA (shRNA) that targets the anti-apoptotic Bcl-2 gene (namely PshRNA) using truncated hepatitis B virus core antigen (tHBcAg) virus-like particle (VLP). A siRNA sequence targeting the anti-apoptotic Bcl-2 was synthesized and cloned into pSilencer 2.0-U6 vector, and encapsidated inside tHBcAg VLP. The VLP encapsidating PsiRNA was conjugated with folic acid (FA) to produce FA-tHBcAg-PsiRNA VLP. Scanning transmission electron microscopy revealed that FA-tHBcAg-PsiRNA VLP has icosahedral structure similar to that of the unmodified tHBcAg VLP. Delivery of FA-tHBcAg-PsiRNA VLP into HeLa cells overexpressing folate receptor (FR) significantly downregulated the expression of anti-apoptotic Bcl-2 at 48- and 72-hours post-transfection. MTT assay demonstrated that the cells’ viability was significantly reduced from 89.46% at 24 h to 64.52% and 60.63%, respectively, at 48- and 72-hours post-transfection. As a conclusion, tHBcAg VLP can be used as a carrier for a receptor-mediated targeted delivery of a therapeutic plasmid encoding shRNA for gene silencing in cancer cells.